2021
DOI: 10.21203/rs.3.rs-865601/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation of Nanostructured HgI2 Nanotubes /Si Photodetector by Laser Ablation in Liquid

Abstract: In this work, HgI2 nanotubes/Si heterojunction has been prepared by pulsed laser ablation in ethanol at laser fluence of 12.7 J/cm2. The structural and optical properties of HgI2 nanotubes (NTs) are studied. The X-ray diffraction (XRD) result shows the presence of the mixture of tetragonal and orthorhombic phases of HgI2. The optical properties results show that the optical energy gap of HgI2 NTs was 2.98 eV measured at room temperature. The photoluminescence (PL) spectra of HgI2 display a single emission cent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The positive Hall coefficient of the B 4 C nanostructure films confirmed that they are p-type, which agrees with the reported data 25 . As shown in Table 2 , the electrical conductivity and mobility of B 4 C nanostructure film decreased as the laser pulses increased as a result of the large concentration of trapping centers and surface states.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The positive Hall coefficient of the B 4 C nanostructure films confirmed that they are p-type, which agrees with the reported data 25 . As shown in Table 2 , the electrical conductivity and mobility of B 4 C nanostructure film decreased as the laser pulses increased as a result of the large concentration of trapping centers and surface states.…”
Section: Resultssupporting
confidence: 92%
“…This parameter is consider is one the most significant figures of merit of the silicon photodetectors 25 . Figure 15 shows the spectral responsivity of B 4 C/p-Si HJs photodetectors measured at a bias voltage of − 5 V prepared at different number of laser pulses.…”
Section: Resultsmentioning
confidence: 99%
“…Pulsed laser ablation in liquid (PLAL) is one of them, and it has been used to make a variety of nanomaterials. It is possible to synthesise a diverse range of nanomaterials, such as semiconductors, metals, ceramics, ides, and diamond-like zinc, by varying laser parameters such as wavelength, laser energy, ablation period, and repetition rate, and these parameters have a significant impact on the shape, size, and morphology of NPs generated by laser ablation in water [8][9][10][11][12]. The method of pulsed laser ablation in liquid has several distinct advantages over traditional physical and chemical nanoparticle preparation methods: (1) the size and shape of the produced nanoparticles can be precisely adjusted during synthesis by manipulating liquids and laser parameters [10]; (2) simple and inexpensive; (3) the final product is typically obtained without any by-products or the need for purification; and (4) using this method, you can create nanomaterial with the desired chemical composition and compound free surfaces [13].…”
Section: Introductionmentioning
confidence: 99%